Analisis Keterpaduan Pasar Buah Lokal dan Buah Impor di Kota Banjarmasin - Luki Anjardiani; Emy Rahmawati; Yusuf Azis (AGRIDES: Jurnal Agribisnis Perdesaan, 2011)
The purposes of this research are to analyse and compare the channels of the local and imported fruit marketing in Banjarmasin, and to analyse the market integrity in channels of the local and imported fruit marketing in Banjarmasin. The channel of the imported fruit marketing from suppliers was continued to retailers around the consumption centers. Meanwhile, the channel of the local fruit marketing from farmers was continued to middlemen then to distributors. The distributors then distributed the fruits to retailers who sold them to costumers. Based on the market integrity analysis, it was known that retailers in A.Yani street have higher market integration with grocers market of imported apple in short run. On the other hand, retailers in Kuripan market have higher market integration with grocers market of local orange in long run.